Synthesis Octyl p-Methoxycinnamate as Sunblock by Transesterification Reaction with the Starting Material Ethyl p-methoxycinnamate - Suzana, .; Irawati, Nunuk; Budiati, Tutuk (Indonesian Research Gateway, 2011)
SynthesisÃÂ octylÃÂ p-methoxycinnamateÃÂ substanceÃÂ asÃÂ sunblock,ÃÂ hasÃÂ beenÃÂ doneÃÂ by transesterificationÃÂ reaction.ÃÂ TheÃÂ startingÃÂ materialÃÂ ofÃÂ theÃÂ reactionÃÂ wasÃÂ ethylÃÂ p-methoxycinnamateÃÂ isolatedÃÂ fromÃÂ KaempferiaÃÂ galangaÃÂ L.TheÃÂ transesterificationÃÂ reactionÃÂ was carried out by reactingÃÂ ethyl p-methoxycinnamate with octanol. The product was identified by UV-VIS,Infra Red and Mass Spectroscopy. The result of measurements on erythemic %T at various concentrations demonstrate that octyl p-methoxycinnamate is applicable as a sunblock compound. KeyÃÂ wordsÃÂ :ÃÂ octylÃÂ p-methoxycinnamate,ÃÂ transesterification,ÃÂ ethylÃÂ p-methoxycinnamate,ÃÂ sunblock